The Control Management of Incidence of Anemia Through Consumption Compliance of Blood Supplementing Tablets in Pregnant Women in Community Health Center - Ai Kustiani; Asep Jalaludin Saleh; Adhi Nurhartanto; Siti Khoirina (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Compliance with iron tablets consumption is one of the factors associated with the incidence of anemia in pregnant women. Anemia is an indicator for poor nutrition and poor health. Anemia in pregnant women is strongly associated with maternal and infant mortality and morbidity, including the risk of miscarriage, stillbirth, prematurity and low birth weight (LBW). This study aims to determine the management of anemia control through adherence to the consumption of blood-added tablets in pregnant women at the Way Laga Health Center Bandar Lampung City in 2021. This type of research is quantitative with a cross sectional design, the population of this study is all pregnant women in the third semester as many as 47 people. with total sampling technique. Data were obtained by using a questionnaire sheet and analyzed by univariate and bivariate with chi square test. The results showed that pregnant women who adhered to the consumption of iron tablets were 44.7%. The results of statistical tests showed that there was a relationship between adherence to iron tablets consumption and the incidence of anemia in pregnant women with a p value of 0.029 (< 0.05).